Identification and Evaluation of Risks in Construction Projects in Archipelagic Areas Using the Failure Mode and Effect Analysis (FMEA) Method A Case Study of East Sumba, Indonesia - Ahmad Farid Ardiansyah (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Construction projects in semi-arid coastal zones operate within complex environmental and managerial constraints that heighten vulnerability to multiple risks. This research analyzes those dynamics through a systematic application of Failure Mode and Effect Analysis (FMEA) to identify, classify, and prioritize critical risk factors affecting project reliability. The results show that material shortages, heat exposure, and unstable energy supply are the most pressing risks, often intensified by weak procurement systems, inaccurate budgeting, and low compliance with environmental and safety protocols. A comparison of managerial and field-level perceptions reveals notable gaps: while both groups recognize similar degrees of severity, on-site workers view risks as more frequent and difficult to detect, reflecting unequal access to information and experience. When combined, the Probability–Impact Matrix and Risk Priority Number assessment indicate that most hazards fall within the high-risk category. The study argues that sustainable construction in such climates requires a move from reactive to anticipatory management. It recommends optimizing local resources through adaptive technologies, reinforcing safety culture and workforce skills, and ensuring transparency via digital governance tools. These integrated measures strengthen resilience, operational reliability, and environmental sustainability in resource-constrained construction contexts